SLOW TO THE GROUND THE TEETH OF THE WORKING UNIT IS ACROSS THE SOIL SOFTENING ZONE STUDY OF THE EFFECT OF SECTION AND ANGLE OF SHOT - Makhmudov Fakhriddin Rakhmonjonovich (World Scientific Research Journal, 2025)
Abstract. One of the most important works in the whole complex of agro-technical measures to prepare the ground for sowing of cotton is harrowing. The article examines the impact of cross-sectional shape and angle of the tooth cusp of a new joint-spike-tooth harrow made of local recycled ferrous metal by casting. Examined the teeth of various cross-sections: square, oval, round. The teeth are wedge-square work surface and different value sharpening angle. The optimal value of the cross-sectional shape and angle of taper of the tooth.